2018
DOI: 10.1093/asj/sjy117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhinoplasty on Labyrinthine Function

Abstract: Background Rhinoplasty is a common surgical procedure that is requested and accepted by patients for cosmetic and functional reasons. Osteotomies are performed on nasal bone, maxillary crest, or vomer to fix the deviations of the nasal dorsum or septum. During the percussion of the osteotomes with the surgical mallet, the vibration energy diffuses to the cranium. Auditory and vestibular systems may be affected by these vibrations. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Tekin et al9 investigated the effect of rhinoplasty on the audiovestibular system and showed that classical osteotomy using a hammer did not affect hearing and balance functions. Similarly, İlhan et al8 reported that the vibratory effect of using the piezoelectric technique during a rhinoplasty did not cause hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tekin et al9 investigated the effect of rhinoplasty on the audiovestibular system and showed that classical osteotomy using a hammer did not affect hearing and balance functions. Similarly, İlhan et al8 reported that the vibratory effect of using the piezoelectric technique during a rhinoplasty did not cause hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…6 Hearing loss after using burr in otologic surgeries has been reported in 3% to 5% in different series. 7 The literature revealed publications stating that the use of piezo and classical osteotome does not negatively affect hearing 8,9 ; however, there is no publication regarding its relationship with hearing despite the widespread use of burrs in septorhinoplasty, as far as we know. Therefore, this study aimed to determine the difference in hearing after the operation in patients who underwent burr-assisted septorhinoplasty, a technique that is used for dorsal reduction and shaping.…”
mentioning
confidence: 99%